Determinants of foreign reserves in Nigeria: An autoregressive distributed lag approach - David Irefin; Baba N. Yaaba (CBN Journal of Applied Statistics, 2011)
On global scale, central banks' holdings of foreign reserves have escalated sharply in recent years. World international reserves holdings have risen significantly from US1.2 trillion in 1995 to nearly US10.0 trillion in June 2011. Dominant among these reserves are concentrated in the hands of few countries. Ten major holders of foreign reserves are mostly from Asia. Oil exporting countries in Africa and the Middle East are not left out in this trend. Nigeria's foreign reserves rose from US5.5 billion in 1999 to US62.40 billion in July 2008, making Nigeria the twenty-fourth largest reserves holder in the world. This pace of reserves accumulation is occurring without regard to its diminishing marginal benefits and rising marginal costs. This study used an Autoregressive Distributed Lag (ARDL) approach to run a slightly modified econometrics "Buffer Stock Model" of Frenkel and Jovanovic (1981) to estimate the determinants of foreign reserves in Nigeria with focus on income, monetary policy rate, imports and exchange rate. The results debunked the existence of buffer stock model for reserves accumulation and provide strong evidence in support of income as the major determinant of reserves holdings in Nigeria.
Keywords: C22; F30; F31; 330; Foreign reserves; central bank; financial crisis; Nigeria